LEGAL DISCOVERY AND JUDGES' LEGAL REASONING IN RESOLUTION OF CORRUPTION CASES IN INDONESIA - Briski Viktor H. Sinaga; Rahmayanti; Derta Simbolon; Lume Hetty Alphani Simbolon (Journal of International Islamic Law, Human Right and Public Policy, 2025)
Corruption is an extraordinary crime that requires a progressive legal approach, including in the process of legal discovery by judges. The complexity of the methods and the development of state losses mean that the application of laws does not always provide certainty in resolving cases. Therefore, legal reasoning is a crucial instrument for emphasizing the principles of justice, certainty, and expediency. This study aims to analyze the legal discovery model in corruption cases and how judges construct legal arguments in their decisions. The research method uses a normative legal approach through analysis of laws, legal principles, and court decisions. The results of the study indicate that legal discovery is necessary in corruption cases involving legal loopholes, multiple interpretations of state losses, and indirect evidence. Legal reasoning can strengthen the legitimacy of decisions and serve as the basis for responsive legal development.